INTEGRATED PETROLEUM RESERVOIR CHARACTERIZATION. THE CASE OF ZHAO57 BLOCK (Es4 + EK1) - Habib, Mukhtar; Xie, Conjiao; Liang, Guang Zheng (FUDMA Journal of Sciences, 2023)
This paper put forward the result of a case studied from a reservoir characterization carried out on Es4+Ek1 reservoir of the Zhao57 block, Zhaozhouqiao oil field, Hebei Province, China. The objective of the study was to accurately create a reservoir model of the oil field and use it to forecast oil and gas production. To achieve this, we characterized the formation by applying integrated geologic and engineering data for the purpose of providing insight understanding of controls on oil and gas production. The formation was first divided into seven groups and fifty four small layers, followed by stratigraphic correlations and quantification of sand thickness. The fifth group was found to be the main oil bearing formation, its top mainly comprise of siltstone while the middle and the bottom comprise mainly of thick layer of massive sand. Sandstone density presents decreasing trend from northwest to south east. Structure model on the fifth group depicts a series of faulting which is believed to be a contributing factor on oil and gas distribution in the group. Average porosity on the fifth group is found to be 7.54%, average permeability is as low as 2.6mD and reserve estimation recorded a value of 82.5364x104t with the V-12 and V-13 layers showing the highest reserve. Result derived from this study will no doubt be useful in respect of further development of the field especially during secondary and tatiary recoveries.
Keywords: Reservoir; Model; Permeability; Porosity; Sand distribution